Dividend catering, life-cycle, and policy: Evidence from Indonesia - Novi Swandari Budiarso; Bambang Subroto; Sutrisno T.; Winston Pontoh (Cogent Economics & Finance, 2019)
This study examines the behavior of firms in Indonesia in relation to the life-cycle and catering theories under the assumption that investors expect optimum returns on stock investments through dividends, capital gains, or both. To this end, we examine 212 firms listed on the Indonesia Stock Exchange during 2010 to 2016 and investigate dividend policy, our dependent variable, in terms of: (1) dividend payers and non-payers and (2) higher, lower, and non-dividend payers. The independent variables in the basic model of this study are retained earnings-over-total-equity, return-on-assets, market-to-book value, firm size, and dividend premium, and the control variables are systematic and idiosyncratic risks. For hypothesis testing, this study conducts two analyses, namely logistic regression and its extension to multinomial regression. The findings confirm that pseudo R-squared and confidence improve under the dividend policy when controlling for risk and dividend payers. We find that mature Indonesian firms pay higher dividends as they are larger and more profitable, with more free cash and insignificant growth opportunities. Conversely, growing Indonesian firms with significant future opportunities pay lower dividends. The findings of this study imply that the dividend policy of mature Indonesian firms supports the life-cycle theory and is inconsistent with the catering theory.
Keywords: G11; G32; G35; 330; dividend policy; life-cycle theory; catering theory; dividend premium; risk; mature firm